(untitled) - HERMANTO (Jurnal Ilmu Manajemen (JIM), 2016)
The purpose of this research is to analyze factors affecting interest rates of working capital loan. The dependent variable in this research is the working capital loan interest rates of state-owned banks and the independent variable is Bank Indonesia Rate, Inflation, Overhead Cost, Net Interest Margin, and Credit Risk.The method used in this research is multiple linear regressions. The population in this study is companies listed in the Stock Exchange (BEI) from 1 January 2005- 31 December 2013. The data collection technique used is documentation. The results of this research shows that simultaneously there is significant influence between the dependent variable to the independent variable. Partially show BI Rate and Inflation affect working capital loan interest rates. Whereas partially Overhead Cost, Net interest, Credit risk not affect the interest rate of working capital loan. Keywords: Working Capital Loan Interest Rate, BI Rate, Inflation, Overhead Cost, Net Interest Margin, and Credit Risk.